Mycoplasma genitalium in asymptomatic patients: implications for screening. Issue 6 (8th July 2009) - Ross, J D C; Brown, L; Saunders, P; Alexander, S
Abstract : Objectives: Mycoplasma genitalium is well established as a cause of urethritis and has also been associated with cervicitis, endometritis and pelvic infection. Low rates of infection suggest screening may be inappropriate in the general population, but it remains unclear whether asymptomatic patients attending a sexual-health clinic should be tested routinely. The objective of this study was to measure the positivity rate of M genitalium infection in asymptomatic individuals presenting to a sexual-health clinic to inform the need for screening in this population. Methods: Asymptomatic patients were identified using a structured questionnaire and tested for M genitalium from genital swabs or urine using two separate polymerase chain reaction (PCR) assays incorporating different primer sequences. Results: 1304 patients were approached over a 6-month period. 743 (57%) patients were symptomatic, and 168 (13%) refused consent, leaving 394 (30%) patients who entered the study. Residual samples were available for 308 (79%) patients, 168 (54%) men and 140 (46%) women. 14/308 (4.5%, 95% CI 2.2 to 6.9%) asymptomatic patients were infected with M genitalium, and an additional 2 (0.6%, 95% CI 0.2 to 2.3%) patients had discrepant PCR results. No significant associations were found between M genitalium infection and age, gender, ethnicity or isolation site. Conclusion: The positivity rate of M genitalium infection in asymptomatic sexual-health clinic attendees is comparable with that of gonorrhoea or chlamydia, and, if evidence of pathogenicity continues to accumulate, a further assessment of the role of routine screening in this setting would be appropriate.